Analytical Analysis of Tubular Adhesive Joints - Pinheiro, A. E. S.; Campilho, R. D. S. G.; Moreira, R. D. F.; Sanchez-Arce, I. J. (Technological Innovation in Engineering Research Vol. 7, 2022)
The fundamental concepts of adhesive joint configurations that apply to flat adherends also apply to tubular adhesive connections, which are used in trusses, piping, and offshore installations. The tensile performance of three adhesives in aluminium tubular joints (AW6082-T651) is compared in this study as a function of various overlap lengths (LO). A numerical analysis employing cohesive zone models (CZM) and the experimentally determined joint strength are both used to compare the findings of an analytical investigation. Two analytical techniques were utilised for the analytical analysis, starting with a simpler and more direct formulation in which peel (\(σ\)y) and shear stresses (\(τ\)xy) were analysed before continuum mechanics criteria were applied to determine the joint strength. While the analytical models displayed certain limitations in relation to the continuum mechanics-based criterion, the CZM results were the most accurate. The CZM approach provides the best approximation, while the global yielding (GY) approach provides identical results.